Does the risk matter? The study of the effect of earnings risk on employee mobility in the labour market - Shelest-Szumilas, Olena (Publishing House of Wroclaw University of Economics and Business, 2021)
This paper attempts to evaluate some implications of the risk of investment in human capital on employee mobility in the United Kingdom. Previous empirical studies showed that the earnings risk affects individual educational and occupational choices. However, the focus was not on the risk associated with investment in job-related training. Given the fact that training benefits for the employee (return on investment) can hardly be predicted accurately, it was hypothesized that financial (earnings) risk has a significant impact on employee labour market mobility. Using the rich panel data from the eighteen waves of the British Household Panel Survey, the study investigated the effect of the risk on employees’ voluntary job changes. The results indicate that the higher risk of investment in job-related training leads to a higher probability of promotion or finding a new job.
Argumenta Oeconomica, 2021, Nr 2 (47), s. 253-269
Keywords: human capital; investment in training; earnings risk; labour market mobility